2022
DOI: 10.3389/fnut.2022.958329
|View full text |Cite
|
Sign up to set email alerts
|

The new exploration of pure total flavonoids extracted from Citrus maxima (Burm.) Merr. as a new therapeutic agent to bring health benefits for people

Abstract: The peel and fruit of Citrus varieties have been a raw material for some traditional Chinese medicine (TCM). Pure total flavonoids from Citrus maxima (Burm.) Merr. (PTFC), including naringin, hesperidin, narirutin, and neohesperidin, have been attracted increasing attention for their multiple clinical efficacies. Based on existing in vitro and in vivo research, this study systematically reviewed the biological functions of PTFC and its components in preventing or treating liver metabolic diseases, cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Irrefutably, herbal medicine and natural products play a vital role in the prevention and treatment of tumors and other systemic diseases 11,12 . Scientists have concluded that herbal medicine treats digestive diseases through inhibiting cell proliferation, inducing apoptosis, anti‐oxidation, and inhibiting inflammatory factors 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrefutably, herbal medicine and natural products play a vital role in the prevention and treatment of tumors and other systemic diseases 11,12 . Scientists have concluded that herbal medicine treats digestive diseases through inhibiting cell proliferation, inducing apoptosis, anti‐oxidation, and inhibiting inflammatory factors 13 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Irrefutably, herbal medicine and natural products play a vital role in the prevention and treatment of tumors and other systemic diseases. 11,12 Scientists have concluded that herbal medicine treats digestive diseases through inhibiting cell proliferation, inducing apoptosis, anti-oxidation, and inhibiting inflammatory factors. 13 Further, herbal medicine and natural products reduce the incidences of tumors, limit recurrence and metastasis, increase the efficacy of chemotherapy drugs, and modulate immune.…”
mentioning
confidence: 99%
“…In addition, by blocking the ERK-P38-JNK signalling pathway, naringin reduces cell metastasis and matrix metalloproteinase (MMP-2) and MMP-9 production in human glioblastoma 14 . Additionally, naringin suppresses angiogenesis and cell migration in GBM cancer by inhibiting MMP-2 and MMP-9 and silencing the signalling pathway-p38 15 . These ndings collectively suggest that naringin may have a multifaceted impact on GBM, affecting various aspects of its progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…fruit, the largest known citrus fruit, is a non-climacteric subtropical fruit belonging to the Citrus family, and widely cultivated in Southeast China (e.g., Fujian, Jiangxi, Zhejiang, Guangdong, and other adjoining provinces) ( Chen et al., 2021 ; Chen et al., 2022 ). Owing to its rich nutrients (e.g., dietary fiber, organic acids, vitamins, pectins, flavonoids and minerals), full succulency, attractive appearance, pleasant flavor, and blessed moral, pummelo fruit is considered as a well-welcomed citrus fruit for consumers ( Nie et al., 2020 ; Ding et al., 2022 ). However, pummelo fruit severs its connection to the tree in terms of water and nutrients after harvest, and must still undergo respiration and other forms of physiological metabolisms, consuming the fruit’s own nutrients and resulting in an acute deterioration in fruit nutritional quality during post-storage ( Nie et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%